High Channel Temperature Mapping Electronics in a Thin, Soft, Wireless Format for Non-Invasive Body Thermal Analysis - Wooyoung Park; Chunki Yiu; Yiming Liu; Tsz Hung Wong; Xingcan Huang; Jingkun Zhou; Jian Li; Kuanming Yao; Ya Huang; Hu Li; Jiyu Li; Yanli Jiao; et al. (Biosensors, 2021)
Hemodynamic status has been perceived as an important diagnostic value as fundamental physiological health conditions, including decisive signs of fatal diseases like arteriosclerosis, can be diagnosed by monitoring it. Currently, the conventional hemodynamic monitoring methods highly rely on imaging techniques requiring inconveniently large numbers of operation procedures and equipment for mapping and with a high risk of radiation exposure. Herein, an ultra-thin, noninvasive, and flexible electronic skin (e-skin) hemodynamic monitoring system based on the thermal properties of blood vessels underneath the epidermis that can be portably attached to the skin for operation is introduced. Through a series of thermal sensors, the temperatures of each subsection of the arrayed sensors are observed in real-time, and the measurements are transmitted and displayed on the screen of an external device wirelessly through a Bluetooth module using a graphical user interface (GUI). The degrees of the thermal property of subsections are indicated with a spectrum of colors that specify the hemodynamic status of the target vessel. In addition, as the sensors are installed on a soft substrate, they can operate under twisting and bending without any malfunction. These characteristics of e-skin sensors exhibit great potential in wearable and portable diagnostics including point-of-care (POC) devices.